Influence of the PMBOK in the optimization of budgets in road infrastructure projects in Lima (LACCEI, 2024)
The general objective of this article is to find a cost control system that, using the PMBOK, can efficiently budget road infrastructure works in Lima 2022. In order to achieve the proposed objectives, firstly, the guidelines for the proposal of a cost control system using the PMBOK to budget road infrastructure works were identified, secondly, the monitoring and control processes that allow budget this type of works and, finally, a guide was determined, so that the cost control system is efficient to budget road infrastructure works in Lima. 2022. The expected results in this research reflected in a guide are translated into an estimated cost of construction of the project, in accordance with the national reality in force at the time of the review and the feasibility of its realization. The conclusions that were obtained were that there is a positive influence of the application of the PMBOK Guide in infrastructure works, reducing costs and optimizing the budgets of this type of works.